2019
DOI: 10.1016/j.ijcha.2019.100370
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory biomarkers in women with non-obstructive angina pectoris and coronary microvascular dysfunction

Abstract: Background Studies that evaluate larger numbers of protein biomarkers in patients with coronary microvascular dysfunction (CMD) have not previously been performed, and very little is known concerning the pathogenetic mechanisms leading to CMD. Our objective was to analyze associations between a broad cardiovascular disease (CVD) protein biomarker assay and CMD, and further explore internal biomarker relations in order to identify possible targets for future treatment interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Multiple studies have linked chronic inflammatory disorders such as lupus, rheumatoid arthritis, and inflammatory bowel disease with higher risk of developing CMD [ 61 63 ]. Others confirmed this result finding a significant correlation between systemic inflammatory markers (mostly plasma CRP) and risk of CMD [ 64 66 ]. Recently, Schroder et al assessed the differential blood protein profile of CMD patients and healthy volunteers.…”
Section: Impact Of Smoking On Coronary Microvasculaturementioning
confidence: 69%
See 1 more Smart Citation
“…Multiple studies have linked chronic inflammatory disorders such as lupus, rheumatoid arthritis, and inflammatory bowel disease with higher risk of developing CMD [ 61 63 ]. Others confirmed this result finding a significant correlation between systemic inflammatory markers (mostly plasma CRP) and risk of CMD [ 64 66 ]. Recently, Schroder et al assessed the differential blood protein profile of CMD patients and healthy volunteers.…”
Section: Impact Of Smoking On Coronary Microvasculaturementioning
confidence: 69%
“…Recently, Schroder et al assessed the differential blood protein profile of CMD patients and healthy volunteers. Interestingly, the main differentially expressed protein biomarkers they found to be associated with CMD were several pro-inflammatory factors, related to the TNF-α-IL-6-CRP pathway [ 66 ]. Smoking is conventionally considered to induce inflammation based on studies who rely on self-reports on smoking status [ 67 70 ].…”
Section: Impact Of Smoking On Coronary Microvasculaturementioning
confidence: 99%
“…In smaller studies we have previously found several biomarkers of inflammation and vascular dysfunction to be associated with non-endothelial dependent CMD in women with angina symptoms but no flow limiting CAD [15,16]. Here we explore the hypothesis that subclinical inflammation is linked to coronary microvascular function and cardiac diastolic function, and that the effect of inflammation on diastolic function is partly mediated by non-endothelial dependent CMD (Fig 1).…”
Section: Introductionmentioning
confidence: 90%
“…Further, increased ROS can contribute to activation of redox-dependent inflammatory mediators exacerbating inflammation. Patients with CMD express higher systemic concentrations of tumor necrosis factor (TNF)-α [ 36 , 37 ]. In fact, TNF-α inhibition in patients with CMD significantly improves CFR [ 38 ].…”
Section: Mechanisms Of Cmdmentioning
confidence: 99%